Assessment of Factors Associated with Generalized Anxiety Disorder and Psychological Distress amid COVID-19 Pandemic: Cross-Sectional Study on the Students of Ras Al Khaimah Medical and Health Sciences University - Bhongade, Bhoomendra; Ali, Areeg Anwer; Adam, Shukri (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Worldwide, the COVID-19 pandemic has caused higher levels of anxiety and psychological distress among university students. To effectively implement interventions in the UAE setting, it is crucial to have an awareness of the factors affecting the mental health of students. In the present study, we evaluated the prevalence of anxiety and psychological distress and the associated factors among medical and health sciences university students amid the COVID-19 outbreak. Materials and Methods: This cross-sectional study was conducted after two weeks from the commencement of the fall 2020 semester with a hybrid method of teaching (online and partially on-site teaching). Through the online survey, we used the generalized anxiety disorder 7-items (GAD-7) and Kessler psychological distress (K10) scales. Results: Out of 309 respondents, students reported moderate to severe GAD [26.2%, Mean=6.75, SE=0.297, 95%CI (6.165; 7.334), Cronbach α 0.898] and psychological distress [40.5%, Mean=23.05, SE=0.527, 95%CI (22.012; 24.087), Cronbach α 0.934]. Feeling lonely was a significantly predicted variable for higher anxiety (β=0.215, 95%CI (0.108; 0.322) and psychological distress (β=0.293, 95%CI (0.175; 0.412). Additionally, online learning from home and COVID-19 news updates were contributing factors to high anxiety. Conclusion: The findings signify the need for the implementation of periodic psychological counseling sessions for university students.
Keywords: COVID-19; Generalized anxiety disorder; Kessler psychological distress; Prevalence; Factors; United Arab Emirates